Peran Guru Sekolah Dasar Dalam Meningkatkan Literasi Dan Numerasi Dasar - Dasan, Sesarius (CV. SINAR HOWUHOWU, 2025)
Basic literacy and numeracy skills are essential foundations for students’ academic development and everyday life. This study aims to analyze the role of elementary school teachers in improving basic literacy and numeracy through instructional strategies, identification of challenges, and innovative classroom practices. A qualitative approach with a case study method was employed, involving two elementary schools located in urban and semi-urban areas in Indonesia. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal that teachers employ various contextual strategies such as shared reading, educational games, and the use of concrete learning tools. Despite facing several challenges, teachers demonstrated initiative by developing additional learning materials and utilizing simple digital tools. The study concludes that teachers play a central role in the success of literacy and numeracy instruction, highlighting the importance of strengthening teacher competence to improve the quality of primary education.